Banking performance assessment / Leny Nofianti ...[et al.] - Nofianti, Leny; Irfan, Andi; Zakaria, Nor Balkish; -, Julina; Eravia, Diana; Ningsih, Rahmita (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2022)
This research developed the Islamic governance model for assessing sharia banking performance management. This research engaged with mixed methods by combining a positive or quantitative paradigm approach and an interpretive paradigm. The quantitative approach was carried out using Factor Analysis with Structural Equation Modeling. Data collection was executed using the observation technique, three in-depth interviews, documentation in building the sharia governance model, and questionnaires distributed to respondents to measure more dominant indicators in building the sharia governance model. The result of the analysis scores demonstrated that the moral and integrity variable exhibited the best goodness of fit model. It was followed by independence and responsible freedom; continuous improvements; honesty; positive thinking; balance, transparency and openness; belief and faith; accountability; professionalism; spirit; management; fulfilment of trust; intelligence; leadership; and justice.